Sosialisasi Model Problem Solving Terhadap Prestasi Belajar Siswa Tema 5 Subtema 1 Keadaan Cuaca Kelas - Hetdy sitio; Tumpal Siahaan; Insenalia Sampe Roly Hutagalung; D Yuliana Sinaga; Debbi Petra Meyana Sitorus; Herlina Sianipar; Meilisa Malik; Winmery L. Habeahan; Jonas Franky Rudianto Panggabean; Ropinus Sidabutar (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of community service aims to determine the effect of using the problem solving model on student achievement in sub-theme 1 class III at SD Negeri 122332 Pematangsiantar. This research uses quantitative research, quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. The experimental unit in this study consisted of 1 class, namely students in class 3C, totaling 25 students at SD Negeri 122332 Pematang Siantar, Pematang Siantar T.A 2022/2023. The test questions will be carried out in class 3C in the same school with a total of 25 students. The results of the data analysis above show that the hypothesis in this study is accepted. There is the influence of the problem solving model on student achievement in theme 5 sub-theme 1 weather conditions at SD Negeri 122332 Pematangsiantar. Based on the results of data analysis after calculating the t test with a significant level of 0.000